Research progress on the roles of lncRNAs in plant development and stress responses - Wang, Xiaoyu; Fan, Hai; Wang, Baoshan; Yuan, Fang (Frontiers in Plant Science, 2023)
Long non-coding RNAs (lncRNAs) are RNAs of more than 200 nucleotides in length that are not (or very rarely) translated into proteins. In eukaryotes, lncRNAs regulate gene expression at the transcriptional, post-transcriptional, and epigenetic levels. lncRNAs are categorized according to their genomic position and molecular mechanism. This review summarized the characteristics and mechanisms of plant lncRNAs involved in vegetative growth, reproduction, and stress responses. Our discussion and model provide a theoretical basis for further studies of lncRNAs in plant breeding.